54.5k views
1 vote
If f(x) = x2 − 2x + 9 and g(x) = 8 − x, what is (f o g)(−4)? A. 111 B. 144 C. 120 D. 129

User Ttarik
by
5.6k points

1 Answer

3 votes

Answer: OPTION D

Explanation:

Given the functions
f(x) = x^2 - 2x + 9 and
g(x) = 8 - x, you need to substitute the function g(x) into the function f(x), then:


(fog)(x)=(8-x)^2 - 2(8-x) + 9

Now, you need substitute the input value
x=-4 into
(fog)(x), then you get the following output value:


(fog)(-4)=(8-(-4))^2 - 2(8-(-4)) + 9


(fog)(x)=(8+4)^2 - 2(8+4) + 9


(fog)(x)=(12)^2 - 2(12) + 9


(fog)(x)=129

This matchis with the option D

User Azul
by
5.5k points